Psikoedukasi regulasi emosi dalam menghadapi stres pada ibu hamil dan ibu dengan anak balita - Deli Yolanda Br Barus; Amalia Juniarly (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Psychoeducation on Emotion Regulation in Coping with Stress in Pregnant Women and Mothers with Toddlers. Psychoeducation on emotion regulation is a very important element in helping individuals cope with stress. Stress experienced by mothers, especially pregnant women and mothers with toddlers, can lead to a decline in the quality of interaction between mother and child. This study aims to conduct psychoeducation activities for the community regarding the importance of emotional regulation in coping with stress in pregnant women and mothers with toddlers, particularly in the Ogan Permata Indah Community Health Center (Puskesmas OPI) area in Palembang. The subjects in this study were pregnant women and mothers with toddlers in the Puskesmas OPI working area in Palembang. Before conducting the outreach activities, the researchers collected field data to determine the conditions and needs of the community in the working area of the OPI Community Health Center in Palembang. The data collection methods used in this study were observation, interviews, and surveys. The analysis technique used to measure the success of these psychoeducation activities was a pre-test and post-test. The results of the study showed an increase in participants' knowledge of emotional regulation strategies in coping with stress, with an average pre-test score of 7.3 and a post-test score of 8.6. These findings indicate that psychoeducation activities are effective in increasing participants' understanding and awareness of emotional regulation, so it is hoped that the adaptive emotional regulation strategies learned can be applied in daily life.